Machine Learning Methods for Engineering Application Development. - Lokulwar, Prasad (Bentham Science Publishers, 2022)
This book is a quick review of machine learning methods for engineeringapplications. It provides an introduction to the principles of machine learningand common algorithms in the first section. Proceeding chapters summarize andanalyze the existing scholarly work and discuss some general issues in this field.Next, it offers some guidelines on applying machine learning methods to softwareengineering tasks. Finally, it gives an outlook into some of the futuredeve.
Description based upon print version of record.
New Information Retrieval System for COVID-19: TREC COVID
Keywords: Machine learning.; Apprentissage automatique.; Machine learning